Competence of Litter Ants for Rapid Biodiversity Assessments. (24th September 2017) - Silva, T. H. Saumya E.; Karunarathna, Nuwan B.; Karunaratne, W. A. Inoka P.
Abstract : Rapid Biodiversity Assessment approaches associated with focusing taxa have overcome many of the problems related to large scale surveys. This study examined the suitability of litter ants as a focusing taxon by checking whether diversity and species assemblages of litter ants reflect the overall picture of arthropod diversity and assemblages in leaf litter in two vegetation types: secondary forest and pine plantation in Upper Hanthana forest reserve, Sri Lanka. In each vegetation type, arthropods were sampled using three sampling methods (Winkler extraction, hand collection, and pitfall traps) along three 100 m line transects. From the two sites, 1887 litter ants (34 species) and 3488 litter arthropods (52 species) were collected. Species assemblages composition of both ants and other arthropods differed significantly between the two sites (ANOSIM, p = 0.001 ) with both groups generating distinct clusters for the two sites (SIMPROF, p = 0.001 ). But there was no significant correlation (p > 0.05 ) between abundance and richness of litter ants and those of other arthropods in both vegetation types. The overall finding suggests that the litter ants do not reflect the holistic picture of arthropod diversity and assemblages in leaf litter, but the quality of the habitat for the survival of all litter arthropods.